An exploration of pain-related vocabulary: implications for AAC use with children. (1st October 2016) - Johnson, Ensa; Bornman, Juan; Tönsing, Kerstin M.
Abstract: Children with significant communication difficulties who experience pain need appropriate means to communicate their pain in order to receive appropriate treatment. Augmentative and alternative communication (AAC) strategies could be used to enable children to self-report pain. The aim of this research study was to identify the common vocabulary children with typical development use to describe physical pain experiences and develop and socially validate an appropriate pain-related vocabulary list for children who use or could benefit from using AAC. A sequential, exploratory, mixed-method design was employed. This paper focuses on the quantitative phase. A set of scenarios was developed to gather pain-related vocabulary appropriate for children aged 6;0–7;11 (years;months) and children aged 8;0–9;11, from 74 children, 61 parents, and 56 teachers. Some 629 pain-related words or phrases were suggested and then classified into seven categories. A composite list of the 84 most frequently occurring pain-related vocabulary items was compiled and socially validated by three adults who used AAC. They emphasized the need to individualize vocabulary and provided suggestions for vocabulary organization for display on any type of AAC system. Despite similarities in the categories of words offered by the various respondent groups, the differences underscore the importance of more than one perspective (particularly that of children and adults) in generating a comprehensive vocabulary list.